1984
DOI: 10.2466/pms.1984.59.3.913
|View full text |Cite
|
Sign up to set email alerts
|

Color Preference and Stimulation Seeking

Abstract: The hypothesis that seekers of high stimulation would prefer the color red and seekers of low stimulation would prefer the color blue was investigated with 170 adolescents. High to low stimulation-seeking was assessed with the Sensation Seeking Scale, red and blue stimulus colors were presented to the subjects and a preference response elicited. Both boys and girls who scored high on the Sensation Seeking Scale preferred the color red and those who scored low preferred the color blue. This provides further con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
3
6
1
Order By: Relevance
“…The cool colors, on the other hand, are thought to produce feelings of spaciousness, restfulness, calm, and peacefulness as compared to the warmer colors. The present results support the first hypothesis of the study and are in accord with the findings of previous research (e.g., Nelson, et al, 1984;Crowley, 1993;Kaya & Crosby, 2006;Manav, 2007). In addition, achromatic color interiors were evaluated more negatively for all the bipolar items except those related to feelings of calm and peacefulness.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The cool colors, on the other hand, are thought to produce feelings of spaciousness, restfulness, calm, and peacefulness as compared to the warmer colors. The present results support the first hypothesis of the study and are in accord with the findings of previous research (e.g., Nelson, et al, 1984;Crowley, 1993;Kaya & Crosby, 2006;Manav, 2007). In addition, achromatic color interiors were evaluated more negatively for all the bipolar items except those related to feelings of calm and peacefulness.…”
Section: Resultssupporting
confidence: 93%
“…Research of color usage in interior design has consistently shown that short wavelength colors are preferred by users, leading to a general association between affective tone and wavelength (Valdez & Mehrabian, 1994). Experimental research has suggested that the cool colors, blue and green, seem to have a relaxing effect and make an interior space seem peaceful, evoking increased perceptions of spaciousness, while warmer hues, such as red and orange, seem to have a stimulating effect, and tend to make an interior seem less spacious (Nelson, Pelech, & Foster, 1984;Whitfield & Wiltshire, 1990;Crowley, 1993). According to a study by Levy (1984), color and emotion are systematically related.…”
Section: Psychological Studies Of Reactions To Colormentioning
confidence: 99%
“…Similarly, Alexander Schauss (1979) reported that use of bright pink tends to reduce aggression and increase relaxation. J. Gordon Nelson (1984) presented evidence confirming the hypothesis that seekers of high and low stimulation respectively preferred the colors red and blue. And Bernard I.…”
Section: Problems Of Interpretationmentioning
confidence: 71%
“…40 However, in some studies, it was set forth that red weakened the performance on intellectual duties. [41][42][43][44] In the study by Nelson, Pelech and Foster 45 with the objective of determining which wave length colors were preferred in the preference of colors by people who were extroverts and introverts, it was observed that persons who had an impulse to high activity preferred red and persons who had an impulse to low activity preferred blue. 46 In the study by Mehta and Zhu 47 using various tasks covering several different domains, they demonstrated that red (HSL color notation 0, 240, 120) (versus blue -160, 240, 120) can activate an avoidance (versus approach) motivation and subsequently, can enhance performance on detail-oriented (versus creative) cognitive tasks.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%